Ultrasonic welding of GF/PA6T composites: Experimental investigation and process optimization. (2021) - Kalyan Kumar, R.; Omkumar, M.
Abstract: Ultrasonic welding (UW) of thermoplastic composites are widely used across manufacturing industries for joining and assembly. For automotive safety component manufacturers, the dimensional requirement of assemblies are critical to meet its functional performance, durability and robustness. This paper presents an application-oriented optimization study to join glass filled high-performance polyamide parts by ultrasonic welding. Process parameters such as vibration amplitude, weld pressure, hold time and weld time were varied both experimentally and statistically to investigate their effect on assembly dimension. Generalized linear model (GLM) in the form of ANCOVA adjusted for covariates effect and response surface method (RSM) with the inclusion of statistically significant covariates were employed for optimization. The confirmatory experimental results are in good agreement with the fitted statistical model.